Valuing Objectivity in Journalism: An Analysis of Kompas TV News Coverage of FPI Activism - Puji Santoso (Jurnal Komunikasi Islam, 2021)
Taking sides in news coverage is considered as consequences of construction process of media reality. According to constructivist approach it is unlikely to avoid subjectivity within news production because of demand of traditional journalistic values such as newsworthy. This study seeks to examine the objectivity of Kompas television news coverage of the Islamic Defenders Front (FPI). Using a qualitative method and constructivist approach in analysing news stories that was linked to reconstruction interviews with journalist, this study found that news stories of FPI activism broadcast by Kompas TV during the 2016-2017 periods were inseparable from subjectivity of journalists while news-making, including resulted from agenda-setting in newsroom.